Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0030222818765813
|View full text |Cite
|
Sign up to set email alerts
|

Can Exposure to Online Conversations About Death and Dying Influence Death Competence? An Exploratory Study Within an Australian Massive Open Online Course

Abstract: A Massive Open Online Course, Dying2Learn, was designed to foster community death conversations and strengthen community awareness of palliative care and death as a normal process. This exploratory study used a pre-post prospective design to determine if participation in Dying2Learn and exposure to online conversations about death and dying resulted in any significant influence on death competence in 134 participants who completed the Coping-with-Death-Scale both at the beginning and end of the course in 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The application of sentiment analysis to death and dying attitudes and emotions represents a unique opportunity to form a deeper understanding about how the public perceive this topic, which is increasing importance to health policy and service delivery. Textual sentiment analysis of how a person describes death can build upon knowledge gained from more traditional self-report measures like surveys [5][6][7][54][55][56] and enable a more comprehensive triangulation of this phenomenon [29].…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of sentiment analysis to death and dying attitudes and emotions represents a unique opportunity to form a deeper understanding about how the public perceive this topic, which is increasing importance to health policy and service delivery. Textual sentiment analysis of how a person describes death can build upon knowledge gained from more traditional self-report measures like surveys [5][6][7][54][55][56] and enable a more comprehensive triangulation of this phenomenon [29].…”
Section: Research Objectivesmentioning
confidence: 99%
“…However, the current evidence base is limited and there have been calls for more rigorous research to better capture public views on dying and death. Understanding contemporary community attitudes and feelings towards death is valuable because it may inform the development of future health services, improve patient and family care at the end-of-life, and it may also inform policy on ways to encourage conversations leading to greater death preparedness and planning [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study on the 2016 Dying2Learn MOOC showed that following the MOOC, participants developed personal insight and better understanding to the topic of death and dying. More importantly, participants also became more comfortable discussing death [8]. It is hopeful that for doctors (and certainly other HCWs) participating in the course, this could translate into better patient care.…”
Section: Doctors' Responses In the Moocmentioning
confidence: 98%
“…To understand the effects of online learning and discussion through a MOOC on participants' attitudes towards death and dying [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation